SATIRE DALAM RUBRIK KUMPARAN, PANDEMI SEMAKIN MENUNJUKKAN POTRET KESENJANGAN PENDIDIKAN INDONESIA, EDISI 11 JULI 2021 - Abdul Aziz (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2022)
This study analyzes comparative language styles in the Kumparan Rubric, Pandemic Shows More Portraits of the Indonesian Education Gap, Author Sarah Novianti, 11 July 2021 Edition of satire consisting of irony, sarcasm and cynicism. This type of research is descriptive-qualitative, with a satire or satire style theory approach. The source of the data for this research is the Kumparan Rubric, Pandemic Shows More Gaps in Indonesian Education, Author Sarah Novianti, July 11, 2021 Edition and the data for this research is that the sentences in it contain several types of satire (satire). Data collection techniques in this study using documentation techniques. The data to be studied has been previously documented, this aims to assist researchers in obtaining the desired data by recording satire (satire) sentences in the form of sentence fragments that have a complete context. Based on the results of data analysis, found the results of several types of satire, irony, sarcasm and cynicism. The most dominant type of comparative language style used from the Kumparan Rubric, Pandemic Shows a Portrait of Indonesian Education Gaps, Author Sarah Novianti, Edition 11 July 2021 is a type of sarcasm style. Based on the findings, it can be concluded that the use of language styles in the Kumparan Rubric, Pandemic Shows a Portrait of Indonesia's Education Gap, Writer Sarah Novianti, July 11, 2021 Edition is more dominant in using the type of satire language style (satire) by using harsh words by replacing good words. be bad words.